2020
DOI: 10.1108/mrr-07-2019-0319
|View full text |Cite
|
Sign up to set email alerts
|

Expectancies and motivational goals of self-initiated expatriates as predictors of subjective assignment achievements and success

Abstract: Purpose Under the framework of the achievement goal and expectancy-value theories, this study aims to examine which motivational goals lead people to self-initiate an international assignment and predict subjective assignment achievements. Design/methodology/approach Data was collected from a convenience sample of 141 self-initiated expatriates (SIEs) from multiple locations. The first set of analyses tested the hypothesis that demographics and expectancies of competence in living and working abroad discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Aryee et al , 1996; Mol et al , 2009; Tharenou, 2003) as well as to the literature on expatriation to dangerous environments (e.g. Bader et al , 2019a, b; Pinto et al , 2020; Suder et al , 2019), yet much more research is still needed. While previous studies have mainly focused on the influence of risk on work outcomes such as performance or attitudes toward host country nationals (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aryee et al , 1996; Mol et al , 2009; Tharenou, 2003) as well as to the literature on expatriation to dangerous environments (e.g. Bader et al , 2019a, b; Pinto et al , 2020; Suder et al , 2019), yet much more research is still needed. While previous studies have mainly focused on the influence of risk on work outcomes such as performance or attitudes toward host country nationals (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the topic of expatriation to dangerous environments has recently attracted increasing attention within the global mobility literature (e.g. Bader et al , 2019a, b; Dickmann and Watson, 2017; Pinto et al , 2020; Suder et al , 2019). Previous studies argue that expatriation to dangerous environments is especially challenging because of the associated exposure to dangers induces stress, strain and fear (Bader and Berg, 2013; Bader et al , 2019a, b; Faeth and Kittler, 2017; Paulus and Muehlfeld, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Jannesari et al (2017) and Hu et al (2019) confirmed proactive personality as a reliable indicator of expatriates' successful cross-cultural adjustment. Pinto et al (2020) found that greater confidence in their capacity to live and work abroad was closely related to SIEs' adjustment. Finally, Jannesari and Sullivan (2019) examined career adaptability, namely an individual’s ability to cope with career changes, as an essential factor in SIEs' adjustment.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 98%
“…This group's expatriation expectations are linked with their career expectations because they expect to find more flexible work arrangements abroad (Reichenberger, 2018;Cook, 2020). Finally, in another recent article Pinto et al (2020) show that SIEs (different professions) expected to pursuit performance goals, but this was more likely the case for SIEs who had greater confidence in their ability to live and work abroad.…”
Section: Findings Careermentioning
confidence: 99%
“…This group’s expatriation expectations are linked with their career expectations because they expect to find more flexible work arrangements abroad ( Reichenberger, 2018 ; Cook, 2020 ). Finally, in another recent article Pinto et al (2020) show that SIEs (different professions) expected to pursuit performance goals, but this was more likely the case for SIEs who had greater confidence in their ability to live and work abroad. The above-discussed articles clearly demonstrate that individuals expect their needs to be fulfilled if they move abroad, but none of these articles demonstrate whether individuals have an active role in triggering their own expectations.…”
Section: Introductionmentioning
confidence: 98%